2019
DOI: 10.14216/kjco.19017
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of proximal upper-third gastric cancer excluding tumors originating in the esophagogastric junction

Abstract: The objective of the current study was to compare surgical outcomes and prognosis based on the longitudinal location of stomach tumors in patients undergoing curative treatment. The specific focus was on the prognosis for adenocarcinomas in the proximal upper-third of the stomach, excluding tumors in the esophagogastric junction (EGJ). Methods: Data from patients who underwent curative treatment for gastric adenocarcinoma between 2000 and 2010 at a single institution were analyzed retrospectively. Excluding tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Tan et al, Zhao et al, and Lee at al. indicated that the location in the upper third part of the stomach was not an independent prognostic factor of poor survival (6,25,26). In this study, the most common location was the upper third part of the stomach (31.9%).…”
Section: Clinicopathological Featuresmentioning
confidence: 52%
See 1 more Smart Citation
“…Tan et al, Zhao et al, and Lee at al. indicated that the location in the upper third part of the stomach was not an independent prognostic factor of poor survival (6,25,26). In this study, the most common location was the upper third part of the stomach (31.9%).…”
Section: Clinicopathological Featuresmentioning
confidence: 52%
“…As we all know, early stages (according to TNM classification) have an influence on better prognosis after gastric cancer resection (6,7,10,25,26,30). Although in studies from the Netherlands and France where stage IV remained stable over the last few years, the staging of TNM of gastric cancer at diagnosis significantly decreased over the last decades (38,(43)(44)(45)(46)(47).…”
Section: Clinicopathological Featuresmentioning
confidence: 99%
“…According to some studies in patients with gastric cancer, tumor location is not an independent prognostic factor significantly affecting survival (9,23,(34)(35)(36)(37). ZeLong et al reported that tumor location within the stomach does not affect the lymph node metastases and overall survival for resectable gastric cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the diagnostics and treatment of early tumor stages according to TNM classification plays a crucial role in the survival of patients with gastric cancer (7,9,12,30,34,35,40,49).…”
Section: Discussionmentioning
confidence: 99%